CRISPR-Cas9 ribonucleoprotein-mediated gene editing in the plant pathogenic fungus Magnaporthe oryzae - McAnany, Tomas; Rowe, David; Huang, Jun; Cook, David E (My University, 2022)
Magnaporthe oryzae, the cause of rice blast disease, is a model fungus for studying plant-pathogen interactions and a major threat to global agriculture. From changes made to their DNA, pathogens like M. oryzae have evolved characteristics like aggressiveness, host range, and fungicide resistance. Once source of DNA variation, arises from DNA repair. There are many sources of DNA damage, with the most severe being double-strand breaks (DSBs) which can lead to genome instability if left unrepaired. Hence, eukaryotes have evolved complex repair mechanisms like microhomology-mediated-end-joining (MMEJ), non-homologous-end-joining (NHEJ) and homologous-recombination (HR) to repair DNA DSBs. Interestingly, these repair pathways have different rates of fidelity, meaning some pathways create more mutations than others. In filamentous fungi, the mechanism by which MMEJ repairs DSBs is not well molecularly characterized, so the purpose of this project is to identify genes controlling MMEJ. To facilitate this, we created knockouts for homologs of DNA repair genes. Five genes were selected for deletion, including ligase 1 A & B, and polymerases θ, 3, and 4. Two CRISPR-Cas9 ribonucleoproteins were used to make DNA DSBs surrounding our target genes. Donor DNA encoding resistance to G418 antibiotic was supplied for insertion into the DSB site, where it served as a selectable marker when plated on complete media containing G418 antibiotics. DNA was extracted from individual colonies and used in PCR genotyping to test for the target gene and correct G418 integration. These knockouts will be characterized in future work to determine their individual roles in MMEJ DSB repair.
Keywords: plant pathology; Magnaporthe oryzae; rice blast; CRISPR-Cas9; DNA repair; USDA NIFA 2019-67032-29071